2013
DOI: 10.14507/epaa.v21n81.2013
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Our Best Choice Right Now”: Examining the Choice Options of Charter School Parents

Abstract: One of the underlying premises of the charter school movement is that quality drives consumer choice. As educational consumers, parents are viewed as rational actors who, if given the choice, will select better performing school. In examining the choice processes of charter school parents, however, this study calls into question the extent to which some parents can make optimal choices. Interviews with parents enrolled in two different charter schools indicate that charter parents do not necessarily choose hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…Expansion of educational options could also be impractical. In rural locales, low population density, limitations on economies of scale, and other human resource impediments may constrain the number of schools that can reasonably be made available to families (Denice & Gross, 2016; Villavicencio, 2013). These potential barriers are worth highlighting since the largest proportion of nonchoosers of district-run public schools in this work were located in small town and rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Expansion of educational options could also be impractical. In rural locales, low population density, limitations on economies of scale, and other human resource impediments may constrain the number of schools that can reasonably be made available to families (Denice & Gross, 2016; Villavicencio, 2013). These potential barriers are worth highlighting since the largest proportion of nonchoosers of district-run public schools in this work were located in small town and rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…A study in St. Louis, Missouri, found that parental school choice is not exercised the same or equally among families of different ethnic groups and socioeconomic status (SES; Goldring & Hausman, 1999). Studies in California, Florida, Tennessee, Louisiana, New York, Pennsylvania, and Washington, D.C., have documented similar results (Arcia, 2006; Beabout & Cambre, 2013; Buckley & Sattin-Bajaj, 2011; Frankenberg et al, 2010; Koedel et al, 2009; Neild, 2005; Roda & Wells, 2013; Saporito, 2003; Villavicencio, 2013). In addition, research has been conducted regarding how American parents choose a school.…”
Section: Literature Reviewmentioning
confidence: 72%
“…Not all parents living in New York City’s choice-rich environment choose a school by weighing different options or applying a comprehensive search process (Villavicencio, 2013). Their charter school selection processes ranged from thorough searches and visits to schools to just filling out a one-page application.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the school choice process, bounded rationality is reflected in parents' different choice sets, the schools that parents actually take into account for their children's schooling (Bell, 2009). The literature has shown that the choice set is also conditioned by the schools parents have access to (economically, geographically, and in terms of information) and by the elements that parents appreciate in the schools, by their preferences (Hastings Kane & Staiger, 2008;Villavicencio, 2013).…”
Section: Introductionmentioning
confidence: 99%